Prominent eustachian valve: An uncommon cause of a common problem during extracorporeal membrane oxygenation support. Issue 1 (22nd November 2020) - Ram, Duvuru; Gillham, Michael; Sibal, Amul K.
Abstract: Suck down events in an extracorporeal membrane oxygenation (ECMO) circuit, due to vein wall being suctioned onto the cannula inflow ports, lead to low circuit flows. These low flow states can be reversed with fluid administration. We present a patient with a prominent eustachian valve (EV) which was encountered while managing the patient on ECMO post lung transplantation for pleuroparenchymal fibroelastosis. We hypothesize that presence of a prominent EV can induce suck down events and needs to be recognized in the differential diagnosis of this problem. This case adds to the literature to increase the awareness of this rare but significant problem.